Opportunity and Means: Horizontal Gene Transfer from the Human Host to a Bacterial Pathogen - Mark T. Anderson (American Society for Microbiology, 2011)
ABSTRACT The acquisition and incorporation of genetic material between nonmating species, or horizontal gene transfer (HGT), has been frequently described for phylogenetically related organisms, but far less evidence exists for HGT between highly divergent organisms. Here we report the identification and characterization of a horizontally transferred fragment of the human long interspersed nuclear element L1 to the genome of the strictly human pathogen Neisseria gonorrhoeae. A 685-bp sequence exhibiting 98 to 100% identity to copies of the human L1 element was identified adjacent to the irg4 gene in some N. gonorrhoeae genomes. The L1 fragment was observed in ~11% of the N. gonorrhoeae population sampled but was not detected in Neisseria meningitidis or commensal Neisseria isolates. In addition, N. gonorrhoeae transcripts containing the L1 sequence were detected by reverse transcription-PCR, indicating that an L1-derived gene product may be produced. The high degree of identity between human and gonococcal L1 sequences, together with the absence of L1 sequences from related Neisseria species, indicates that this HGT event occurred relatively recently in evolutionary history. The identification of L1 sequences in N. gonorrhoeae demonstrates that HGT can occur between a mammalian host and a resident bacterium, which has important implications for the coevolution of both humans and their associated microorganisms. IMPORTANCE The interactions between microbes and their hosts are relevant to several aspects of biology, including evolution, development, immunity, and disease. Neisseria gonorrhoeae serves as a particularly informative model for this interaction because it has exclusively coevolved with humans and is not known to be found in any other environment. In addition, investigation of the evolutionary relationship between N. gonorrhoeae and humans has practical implications, since gonorrhea is a prevalent sexually transmitted infection worldwide. This study was undertaken to characterize the horizontal transfer of genetic information from humans to N. gonorrhoeae, an event that has been scarcely recognized between any mammalian host and bacterial pathogen. Here we provide evidence that this genetic exchange was the result of a recent evolutionary event that has been propagated within the gonococcal population.